2000
DOI: 10.1021/bi002315x
|View full text |Cite
|
Sign up to set email alerts
|

The Mitochondrial Copper Metallochaperone Cox17 Exists as an Oligomeric, Polycopper Complex

Abstract: Cox17 is the candidate copper metallochaperone for delivery of copper ions to the mitochondrion for assembly of cytochrome c oxidase. Cox17 purified as a recombinant molecule lacking any purification tag binds three Cu(I) ions per monomer in a polycopper cluster as shown by X-ray absorption spectroscopy. The CuCox17 complex exists in a dimer/tetramer equilibrium with a 20 microM k(d). The spectroscopic data do not discern whether the dimeric complex forms a single hexanuclear Cu(I) cluster or two separate trin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

11
113
0
3

Year Published

2004
2004
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 116 publications
(132 citation statements)
references
References 28 publications
(55 reference statements)
11
113
0
3
Order By: Relevance
“…Protein Purification-Recombinant Cox17 was purified as described previously by Heaton et al (14). E. coli BL21 (DE3) transformants with COX17 on a pAED3 vector were used for the Cox17 purification using conventional chromatography on an AKTA fast protein liquid chromatography unit (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Protein Purification-Recombinant Cox17 was purified as described previously by Heaton et al (14). E. coli BL21 (DE3) transformants with COX17 on a pAED3 vector were used for the Cox17 purification using conventional chromatography on an AKTA fast protein liquid chromatography unit (Amersham Biosciences).…”
Section: Methodsmentioning
confidence: 99%
“…The roles of Cox17, Sco1, and Cox11 in copper metallation of CcO were substantiated by the observation that each protein is a Cu(I)-binding protein and that mutations that abrogate in vivo function attenuate Cu(I) binding (11,(13)(14)(15). Cox17 is a soluble protein that localizes within the IMS and also within the cytoplasm (8).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The scarcity of Cu I clusters bound by organothiolates in biological systems, such as those that drive Mt Csp3 Cu I core formation, is surprising given their rich coordination chemistry18, 19 and the thiophilic nature of Cu I . Proteins involved in copper homeostasis, particularly in Saccharomyces cerevisiae , have been found to bind tetranuclear Cu I clusters in vitro using Cys residues, but no crystal structures are available 20, 21, 22, 23, 24. Extended X‐ray absorption fine structure data for these are similar to that of [Cu 4 (SPh) 6 ] 2− 20, 21, 23, 25.…”
mentioning
confidence: 99%
“…Cox17 is found in both the cytosol and mitochondria. It was originally thought that Cox 17 binds copper in the cytosol, translocates into mitochondria and delivers copper to Cox1 and Cox2 [48][49][50]. However, further studies in yeast showed that in Cox 17 deficient cells, CcO activity can be fully restored by mitochondrial restricted expression of Cox17 [51].…”
Section: Copper Metabolism In Eukaryotic Cellsmentioning
confidence: 99%